Exhibit highlighting Colorado State University Libraries Archives and Special Collections: University Archives - McClelland, Deborah Ann, artist; Colorado State University. Archives and Special Collections, author (Colorado State University. Libraries, 2018)
Display items from the fourth of four exhibit cases featuring Colorado State University Libraries' Archives and Special Collections. Focusing on the University Archives, included are sketches from the diaries of Elijah E. Edwards, first president of Colorado State University from 1879 through 1882. A summary is given of Edwards' background.
University Archives: exhibit highlighting Colorado State University Libraries Archives and Special Collections
Keywords: Colorado State University -- History; Colorado Agricultural College; Edwards, E. E. (Elijah Evan), 1831-1915; sketches; Exhibitions; 19th century; Diaries; Drawings